EFFECTIVENESS OF INTERACTIVE MULTIMEDIA-BASED ANIMATED VIDEO EDUCATION ON BREAST SELF-EXAMINATION KNOWLEDGE AMONG ADOLESCENT GIRLS : EFEKTIVITAS VIDEO ANIMASI EDUKASI BERBASIS MULTIMEDIA INTERAKTIF DALAM MENINGKATKAN PENGETAHUAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PUTRI - Tri Endah Pangastuti; Dina Carolina Hapsari; Shilpa Puspita; Nelly Yardes; Santa Manurung; Wartonah Wartonah; Ace Sudrajat; Nadhia Elsa Silviani; Eska Riyanti; Dewi Lusiani (Journal of Health and Cardiovascular Nursing, 2026)
Breast cancer is a leading cause of worldwide female morbidity and mortality, making early detection through Breast Self-Examination (BSE) crucial for adolescents despite their limited awareness. This quasi-experimental study with a pretest–posttest control group design evaluated the effectiveness of interactive multimedia animation video education in improving BSE knowledge among adolescent girls. Seventy participants aged 16–20 were divided into an intervention group (animated video) and a control group (standard leaflet). Knowledge was measured via a validated questionnaire ($α = 0.772$) and analyzed using Wilcoxon and Mann–Whitney U tests ($p < 0.05$). Results showed a significant knowledge increase in the intervention group from 5.0±1.36 to 9.28±0.85 ($p < 0.001$), while the control group showed no significant improvement ($p = 0.065$). The difference between groups was highly significant ($p < 0.001$). In conclusion, interactive multimedia animation video education is more effective than conventional leaflets, offering a practical strategy to enhance adolescent reproductive health literacy.